2011
DOI: 10.1186/cc10198
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Brazilian-Portuguese version of three tools to diagnose delirium: CAM-ICU, CAM-ICU Flowsheet and ICDSC

Abstract: Introduction Noninvasive ventilation is a safe and eff ective method to treat acute respiratory failure, minimizing the respiratory workload and oxygenation. Few studies compare the effi cacy of diff erent types of noninvasive ventilation interfaces and their adaptation. Objective To identify the most frequently noninvasive ventilation interfaces used and eventual problems related to their adaptation in critically ill patients. Methods We conducted an observational study, with patients older than 18 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
0
20

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(81 citation statements)
references
References 0 publications
6
55
0
20
Order By: Relevance
“…Although several investigators have independently demonstrated that the CAM-ICU has a high sensitivity and specificity, the CAM-ICU in these studies was usually administered by research personnel (37,38,(60)(61)(62)(63)(64)(65). A multisite Dutch study, comparing the CAM-ICU administered by ICU nurses against three delirium experts using DSM-IV criteria, demonstrated a CAM-ICU sensitivity and specificity of 47% and 98%, respectively (66).…”
Section: Discussionmentioning
confidence: 98%
“…Although several investigators have independently demonstrated that the CAM-ICU has a high sensitivity and specificity, the CAM-ICU in these studies was usually administered by research personnel (37,38,(60)(61)(62)(63)(64)(65). A multisite Dutch study, comparing the CAM-ICU administered by ICU nurses against three delirium experts using DSM-IV criteria, demonstrated a CAM-ICU sensitivity and specificity of 47% and 98%, respectively (66).…”
Section: Discussionmentioning
confidence: 98%
“…Despite the existence of a Brazilian Portuguese translation of the CAM, the translation and adaptation of this instrument for the European Portuguese population is necessary, bearing in mind the significant lexical, syntactical and semantic differences between the two varieties of Portuguese. Moreover, important Brazilian studies on CAM-ICU (23), an adaptation for intensive care units, have been recently published (24)(25)(26), along with a previous European Portuguese translation (27), showing the evident socio-cultural differences.…”
Section: Discussionmentioning
confidence: 99%
“…The original CAM-ICU in English was validated in three large cohort studies of patients with a sensitivity of 95% to 100%, specificity of 89% to 93% and high interobserver reliability. Its translation and validation to Portuguese occurred in 2011, with sensitivity and specificity of 72.5% and 96.2%, respectively (5) , and agreement among evaluating nurses at 100%. It incorporates the four characteristics of the original instrument (4) , where the delirium is identified when about three of these characteristics are present (4) .…”
Section: Introductionmentioning
confidence: 99%